UNEQUAL DISTRIBUTION OF HOUSEHOLD TASKS IN THE WORKING MOTHER-THEMED NOVELS - Dewi, Maya Kurnia; Pratama, Mochamad Rizqi Adhi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
In many countries, the rate of women’s participation in labor keeps increasing from time to time because of their educational level and economic condition. This condition leads to some changes concerning the gender roles in a family. However, it does not change the division of household tasks between husband and wife. Women are still considered responsible for doing most of the household tasks. This topic is often presented as the central theme in some literary works, particularly novels. This research examines three different novels, Opening Belle, I Don’t Know How She Does It, and The Balance Project, by analyzing the inequality in dividing household tasks faced by the working mothers in the novels. This research uses a qualitative method consisting of description, reduction, and selection stages. The analysis results show that the working mothers still do most household tasks, while their husbands do not help them much. Although they can pay someone to help them do the tasks, however, the help is not as good as expected. They still have to struggle in combining household tasks and work, which eventually makes them feel exhausted.